Constitutional amendments in India 1950-1989 - Raman, Sunder (Calcutta, 1989)
A democratic constitution founded on the principle of popular sovereignty must make possible the assertion of people's will as changing circumstances demand from time to time. The framers of the Constitution of India made the enabling provsion in Article 368. Availing of this provision, sixty-one amendments have been made with few more in the offing. A large number of these have to do with socio-economic reforms, some of them specially to meet and overcome the effect of judicial invalidation of social legislations and executive actions. These amendments, themselves add up to, so to say, a mini constitution. In this work an attempt has been made to appreciate the amending power in the context of democracy. Further, the author has discussed threadbare, the spirit in which the amending process was envisaged by the founding fathers. Dr. Ambedkar's proposal to effectuate changes in the Constitution, the original Article 368 and the changes brought therein etc. The work includes, besides, the text of all the constiutional amendments with their Statements of Objects and Reasons. A very useful and handy work for researchers, academics and practising lawyers.
Keywords: Constitutional amendments